Anomalous pigmentation in a dusky dolphin Lagenorhynchus obscurus from Golfo Nuevo, Argentinian Patagonia (Revista de Biología Marina y Oceanografía, 2023)
Anomalous pigmentation conditions occur with low frequency in marine mammals. Here is presented the first known record and resighting of a hypo-pigmented all-white dusky dolphin from Golfo Nuevo off Península Valdés, Argentinian Patagonia. The anomalously pigmented Lagenorhynchus obscurus was observed three times between 2016 and 2018. Images suggest that this could be a case of a leucistic dusky dolphin, apparently a single individual. The hypo-pigmented individual was estimated to have reached adult body size, and was probably sexually mature. More research is required for a proper understanding of the effect on behavioral, ecological and physiological conditions.